GANGGUAN PEMEROLEHAN KOSAKATA BAHASA PADA ANAK DOWN SYNDROME DALAM KAJIAN PSIKOLINGUISTIK - Nur Fadhilah, Rosadina; Arsanti, Meilan (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
Discussion of the role of language in human life and focuses on children withdown syndrome, a genetic disorder that affects language development. This disorder involves difficulties in the production of verbal speech, which stems from a pampering family environment and a school environment that encourages independence. This research adopts a quantitative descriptive method with a focus on case studies of children withdown syndrome named Qinis, aged 2 years 8 months. Despite facing obstacles in pronunciation of vowels, Qinis showed positive progress in understanding and using words. The implications of the findings involve therapist support and active parental participation to overcome children’s language barriersdown syndrome through a holistic approach. This article highlights the urgency of understanding language in forming social relationships and provides insight into efforts to improve children’s communication skillsdown syndrome.